2011
DOI: 10.5941/myco.2011.39.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of Marssonina coronaria Associated with Apple Blotch Disease

Abstract: Marssonina coronaria associated with apple blotch disease causes severe premature defoliation, and is widely distributed in Korea. Thirteen isolates were collected from orchards located in Gyeongbuk Province from 2005~2007. All isolates displayed over 99.6% and 99.2% sequence similarity to each other in internal transcribed spacer regions and partial sequences of 28S rDNA, respectively. The isolates were phylogenetically closely related to Chinese isolates. Selected isolates did not differ in their pathogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
2
37
0
2
Order By: Relevance
“…Conidia, obovoid, hyaline, a septate, ranged between 14.8-21 x 3.5-5.3 µm in size. This characteristic is similar to M. coronaria that described by Lee et al (2011), however there are differences in the size of the conidia. When conidia were germinated in sterile water medium on a glass slide convex, then within six hours, it formed germ tubes.…”
Section: Biological Studies Of Marssonina Coronaria Morphological Chasupporting
confidence: 68%
See 2 more Smart Citations
“…Conidia, obovoid, hyaline, a septate, ranged between 14.8-21 x 3.5-5.3 µm in size. This characteristic is similar to M. coronaria that described by Lee et al (2011), however there are differences in the size of the conidia. When conidia were germinated in sterile water medium on a glass slide convex, then within six hours, it formed germ tubes.…”
Section: Biological Studies Of Marssonina Coronaria Morphological Chasupporting
confidence: 68%
“…Similar results are presented by Zhao et al (2010) show that the potato carrot dextrose broth(PCDB) and potato carrot broth sucrose (PCSB) are suitable for M. coronaria (teleomorph: Diplocarpon mali) in cases of mycelial growth and production of conidia. Meanwhile the results of Lee et al (2011) shows the highest mycelial growth is observed on mannose and bacto-peptone amended media with colonies 9.0 and 18.5 mm in diameter resulted by using the carbon and nitrogen sources. Pyridoxine and biotin are the best vitamins, while FeSO4 and FeCl3 are the best mineral salt sources for mycelial growth to produce the highest dry mycelial weight.…”
Section: The Suitability Of M Coronaria On Eight Artificial Mediamentioning
confidence: 98%
See 1 more Smart Citation
“…Apple blotch diseases caused by M. coronaria have been reported in many countries including Korea (Lee and Shin, 2000;Sharma, 2000;Tamietti and Matta, 2003;Lee et al, 2011). Furthermore, Korean isolates were very similar to Japanese and Chinese isolates, where the disease has caused a significant production problem over the past few years (Lee et al, 2011). According to previous reports, the leaves are the main photosynthetic organs in plants, and as such, are closely associated with photosynthetic function.…”
Section: Introductionmentioning
confidence: 94%
“…However, among these diseases the mosteconomically important in Korean orchards are apple blotch and alternaria leaf spot (Lee et al, 2007). Apple blotch diseases caused by M. coronaria have been reported in many countries including Korea (Lee and Shin, 2000;Sharma, 2000;Tamietti and Matta, 2003;Lee et al, 2011). Furthermore, Korean isolates were very similar to Japanese and Chinese isolates, where the disease has caused a significant production problem over the past few years (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 96%